Sustainable Marketing Strategies to Empower Stingless Bee Honey Agripreneurs for Competitive and Inclusive Agribusiness Growth - I Putu Gede Didik Widiarta; Riki Andika; I Kadek Sudiarsana; Dinar Anindyasari; Lestari Gita Nur’aini (Indonesian Journal of Sustainable Agriculture and Environmental Sciences (IJSAES), 2025)
Background: Stingless bee honey presents a high-value niche within sustainable agrifood systems, yet small-scale agripreneurs face structural constraints in marketing, certification, and digital engagement that impede inclusive competitiveness. Aim: This study formulates sustainable marketing strategies to empower stingless bee honey agripreneurs in Samarinda, East Kalimantan, thereby enhancing market access, firm-level resilience, and socio-ecological sustainability. Methods: Employing a convergent mixed-methods design, primary data were collected between July and September 2025 through 27 semi-structured interviews, three focus group discussions (FGDs), direct observation, and structured questionnaires involving 65 agripreneurs, eight cooperative leaders, and six local government or institutional stakeholders. Participants were selected using a purposive sampling strategy to ensure representation across enterprise scales and cooperative membership. Internal and external determinants were assessed using IFE and EFE matrices; results were integrated via IE and SWOT frameworks to derive strategy clusters. Results: The IFE (score = 2.86) and EFE (score = 2.93) positions indicate a “Growth and Build” strategic posture. Four strategy clusters emerged: SO (eco-branding, certification, tourism linkages, e-commerce expansion), WO (digital literacy, quality assurance, managerial capacity building, inclusive finance), ST (value-chain diversification, R&D partnerships, sustainability differentiation, cooperative logistics), and WT (community microfinance, joint marketing, insurance/risk-sharing, partnership models). Triangulation of qualitative and quantitative findings strengthens the validity of these strategic priorities. Conclusion: Integrating sustainability principles with digital marketing and cooperative governance offers a viable pathway for transforming stingless bee honey firms into resilient, inclusive agribusinesses. Policy and institutional support that bolsters access to certification, digital capacity, and cooperative finance are pivotal in translating ecological strengths into competitive market outcomes.